Debate Between Individual Expectations and Experience Inside the National Idea of Integration: a Literary Study - Bhattacharjee, Debraj (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2024)
This paper examines the philosophical tension between individual expectations and national integration during the transition from colonialism to sovereign democracy. The emergence of anarchism, both at the social periphery and in the redefinition of colonial myths, posed significant challenges to the national idea of integration. Concurrently, Nietzschean philosophy, supported by Tagore well before the constitution was enacted, influenced radical thought, further complicating the integration process. This created a dilemma, leading to the establishment of a doctrine to balance individual autonomy with the demands of a democratic social order. The study aims to explore these philosophical interventions to provide a deeper understanding of individual constitutional values as manifested in literary works. Through a qualitative analysis of relevant literary texts and historical documents, the research uncovers the complexities of integrating individual and collective values in the formation of a democratic society. The findings reveal that the interplay between anarchism and Nietzschean thought significantly shaped the discourse on individual rights within the emerging constitutional framework. The study concludes that these philosophical interventions played a critical role in defining the space for individual engagement within the democratic order. This research contributes to the broader discourse on the philosophical underpinnings of constitutional values and their literary expressions, offering insights into the evolving relationship between individual autonomy and democratic governance.